Case Study : Genius Wisdom / Mohamad Hazwan Haziq Hazmawi - Hazmawi, Mohamad Hazwan Haziq (2021)
Genius Wisdom is a big corporation that manufactures dental instruments, and it is the country's first company. Before this business, the only company that manufactured local goods was a rubber glove factory, so Mr. Zulkifli Hussin, the owner of the company I interviewed, came up with the idea to make the first dental appliance, a dental chair.